Transient Sulfenic Acids in the Synthesis of Biologically Relevant Products - Barattucci, Anna (Molecules, 2018)
Sulfenic acids as small molecules are too unstable to be isolated and their transient nature offers the possibility to involve them in concerted processes that lead to the obtainment of functional groups such as sulfoxides, sulfones, and disulfides. All these functions are present in a number of natural and synthetic drugs and can represent structural motives inducing biologically relevant properties. In this small review the generation and reactions of sulfenic acid bearing naturally occurring residues are described. Carbohydrate and aminoacid-derived sulfenic acids have been used in concerted addition with triple bonds to obtain alliin derivatives and thiosugars in enantiomerically pure form. Glycoconjugates with sulfinyl, sulfonyl, and disulfane functional groups and pyridine-derived disulfides have been obtained from bis- and tris-sulfinyl precursors of sulfenic acids. Small families of such compounds have been subjected to preliminary biological tests. Starting from the evidence that the control of molecular architecture and the presence of suitable functional groups can play a significant role on the exhibition of biological properties, apoptotic effects on malignant cells by glycoconjugates and inhibitory activity against the important human pathogen S. aureus by pyrimidine-derived disulfides have been found.